1982
DOI: 10.1227/00006123-198202000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Anatomy of the Posterior Inferior Cerebellar Artery

Abstract: Fifty cerebellar hemispheres from 25 adult cadavers were examined. The posterior inferior cerebellar artery (PICA), by definition, arose from the vertebral artery. The vertebral artery was present in 49 and the PICA was present in 42 of the 50 hemispheres. Forty-one of the 42 PICAs arose as a single trunk and 1 arose as a duplicate trunk. The PICA was divided into five segments: the anterior medullary segment lay on the front of the medulla; the lateral medullary segment coursed beside the medulla and extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
0
10

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 387 publications
(108 citation statements)
references
References 0 publications
3
95
0
10
Order By: Relevance
“…In 16% of cases [2], only 1 PICA can be identified. Typically, it supplies blood to the caudal medulla, cerebellar tonsil, inferior portion of the cerebellar hemisphere and vermis, and the choroid plexus of the 4th ventricle [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 16% of cases [2], only 1 PICA can be identified. Typically, it supplies blood to the caudal medulla, cerebellar tonsil, inferior portion of the cerebellar hemisphere and vermis, and the choroid plexus of the 4th ventricle [10].…”
Section: Discussionmentioning
confidence: 99%
“…While most PICA aneurysms originate from the PICA-vertebral artery junction and comprise up to 3% of all intracranial aneurysms [1, 12], distal locations along the PICA are less common and represent 0.5 to 1.0% of all intracranial aneurysms [2, 3, 13]. Some authors [1]have suggested that approximately two thirds of PICA aneurysms occur at the PICA-vertebral junction and that one third occurs more distally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations